Identification of bacteria causing mastitis in a dairy goat farm located in Tequisquiapan, Querétaro, Mexico: Mastitis caprina en Tequisquiapan, Querétaro - Ruiz-Romero, Angelica; López-Martínez, Maribel Esperanza; Arriaga-Avilés, Yazmín Ivonne; Díuaz- (Ecosistemas y Recursos Agropecuarios, 2024)
Mastitis is the inflammation of the mammary gland. The objective of this work was to perform the California Mastitis Test (CMT), evaluate the somatic cell count (SSC) and the composition of milk to determine the relationship with the bacterial agents identified in a production unit in Tequisquiapan, Querétaro, Mexico. Twenty goats (French Alpine and Toggenburg) were evaluated; 166 milk samples were obtained, the prevalence of subclinical mastitis was 30%; Staphylococcus species with the highest prevalence in the sampled goats were S. chromogenes and S.warneri. An association was found between bacterial growth and the CMT; no significant differences were found between the SSC and the CMT and neither between the percentage of fat, protein, lactose and total solids.